BANTUAN LUAR NEGERI JEPANG DALAM MENGURANGI EMISI GAS RUMAH KACA DI INDONESIA MELALUI PROGRAM COOL EARTH PARTNERSHIP PERIODE 2008-2012 - Liya Sundari (2021)
The phenomenon of climate change occurs almost all over the world, especially with developing countries, one of which is Indonesia. Japan, as an annex-1 country, is the largest emitter of GHG (greenhouse gases) in the world and has the obligation to reduce GHG emissions through JICA (Japan International Corporation Agency), providing ODA (development assistance from Japan) in the form of a Cool Earth Partnership loan to help Indonesia reduce emission level grk. This research uses qualitative research and descriptive research, examined through the theory of bilateral cooperation, environmental cooperation and foreign aid theory. The implementation of Japanese foreign assistance in reducing greenhouse gas emissions in Indonesia through the Cool Earth Partnership program for the period 2008-2012 in the form of loan funds aimed at facilitating national policies through a policy matrix (mitigation, adaptation, cross-sectoral issues) to reduce GHG emissions. The obstacles and obstacles to implementation are the lack of coordination between the Indonesian government and the Japanese government (JICA) regarding the evaluation of ODA implementation, the lack of participation of local governments and the public, and the less than optimal absorption of the budget. These things made JICA decide to discontinue ODA to Indonesia. The occurrence of obstacles and obstacles, among others, is because the local government and the community do not feel involved from the beginning of program planning, and the program is not in accordance with the local Regional Autonomy Law. Japan's foreign aid (ODA) is very helpful for Indonesia in facilitating national policies, many activities and activities have been carried out to reduce GHG emissions. However, the achievements provided have not been maximized, because the implementation of the policy matrix is still not optimal.